Editorial – Special Issue: IndigMEC, Indigenous Mathematics Education Conference. Tromsø, Norway, September 4–7, 2017 - Fyhn, Anne Birgitte (North American Study Group on Ethnomathematics, 2017)
Source at https://journalofmathematicsandculture.wordpress.com/2017/12/28/journal-of-mathematics-and-culture-volume-11-number-3/ .